(untitled) (Journal of Fiber Bioengineering and Informatics, 2009)
This paper reports the study of rheological properties of the urea denatured soybean protein in concentrations of 10 % after 0 mol L^-1 ∼ 10 mol L^-1 urea treatment using a programmable control revolving viscometer (Brookfield RVDV-II+/SSA-SCL27). A theoretical foundation is provided in this paper to study the exploitation and application of soybean protein. The results show that after urea denaturation the soybean protein solution was a typical pseudoplastic fluid while before it was a Bingham character fluid. The viscosity of both decreased with shear rates and increased with urea contents. The change was much obvious at the urea concentration of 4 mol L^-1 ∼ 6 mol L^-1. After urea denaturation, the non-Newtonian index of soybean protein solution increased from 0.17 to 0.3 ∼ 0.4 at 20°C, which was still fairly low. The stabitily of fluids was pretty bad. The viscosity dropped with temperature significantly.